2001
DOI: 10.1177/00220345010800101101
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Compromised Bonding to Oxidized Etched Dentin

Abstract: The mechanism responsible for hydrogen-peroxide- or sodium-hypochlorite-induced reductions in dentin bond strength is unknown. This in vitro study tested the hypothesis that these oxidizing agents were responsible by attempting to reverse the effect with sodium ascorbate, a reducing agent. Human dentin was treated with these oxidants before or after being acid-etched and with or without post-treatment with sodium ascorbate. They were bonded with either Single Bond or Excite. Hydrogen peroxide reduced the bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
364
4
52

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(434 citation statements)
references
References 22 publications
14
364
4
52
Order By: Relevance
“…The results revealed that the exposure of dentin to peroxide decreased the bond strength, as reported in several previous studies [15,16,23,27] (Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…The results revealed that the exposure of dentin to peroxide decreased the bond strength, as reported in several previous studies [15,16,23,27] (Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…In studies carried out by Lai and others, [15][16] it was reported that the bond strength of enamel decreased after bleaching treatment. However, when the bleaching treatment was followed by treatment with sodium ascorbate, bond strength returned to its normal values.…”
Section: Introductionmentioning
confidence: 96%
“…14 However, in order to remove the dissolved peroxide remnants on bleached enamel, it has been demonstrated that the application of a catalase or 10% sodium ascorbate on bleached enamel and dentin immediately after the bleaching treatment makes the above mentioned waiting periods unnecessary. [15][16]26 Parallel to these studies, the current authors have demonstrated in studies that the application of 10% sodium ascorbate solution on bleached enamel and dentin could be an alternative to delayed bonding. [17][18][19][20] In previous studies by the current authors, it was determined that 10% sodium ascorbate solution applied to the enamel surface for 10 minutes increased bond strength on the surface on which it was applied.…”
mentioning
confidence: 93%
“…Sodium ascorbate presents low toxicity and has a neutral pH (approximately 7), being appropriate for use on dental structures without producing undesirable damages (23). The reaction between SA and oxygen into dentin peaks within 1 min and thereafter the reaction reduces considerably (2).…”
Section: Immediate Bonding To Bleached Dentinmentioning
confidence: 99%